PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN KEWIRAUSAHAAN BERBASIS POTENSI ALAM SETEMPAT - Lilis Karwati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
The limited ability of women is a very crucial problem in the community, especially in fulfilling their daily needs due to the gap between the required ability and the low the ability they have. The main priority in improving the women’s life quality is by providing that can improve their ability to utilize the local natural resources for commercial purposes. The purpose of this study is to describe the process, outcome and effects of the training. Applying quantitative and qualitative approach and descriptive method, this study was conducted in LKP Yuniza Desa, Kecamatan Salawu in August 2016. The data was collected by using participative observation, interview, and document study. Research subjects included learning community members, tutors, and LKP’s management. The result of the study indicate women can be empowered through enterpreneurship training which provide them with knowledge, attitude, and skills enabling them independent and self employed to improve their life quality.